Ergot alkaloids: From witchcraft till in silico analysis. Multi-receptor analysis of ergotamine metabolites. (2015) - Dellafiora, Luca; Dall'Asta, Chiara; Cozzini, Pietro
Graphical abstract: Abstract: The term Ergot is referred to the sclerotium of ascomycetes – a protective kernel produced during resting stage of some fungi – which replaces seeds of susceptible cereals and plants intended for human and animal diet. It contains various composition of tryptophan-derived toxins defined ergot alkaloids. Since sclerotia can be harvested and milled together with cereals, they represent a source of food and feed contamination after breakage and spreading of mycotoxins into the various milling fractions. The effects of ergot alkaloids, including those adverse for human health, have been known since the Middle Ages. Nevertheless, as recently stated by the European Food Safety Authority, further information is needed on metabolism and target receptors-binding of common alkaloids in food. Unfortunately, the experimental investigation is challenging due to the high costs in terms of time and money. This study was thus aimed at assessing whether the in silico modeling can be an effective tool to investigate the interaction between multiple serotonin receptors and a wide set of ergotamine metabolites, including experimentally detected molecules and predicted derivatives. Validated models provided precious insights about the effects exerted by metabolic modifications on the receptor–ligand interaction. Such structural information may be useful to support the design of further experimental analysis.